Peran Keluarga Dalam Merawat Lansia Dengan Hipertensi Di Posyandu Tandun - Lora Marlita; Saniya; Eka Putri Setya Ningsih (Jurnal Keperawatan Abdurrab, 2026)
Elderly people with hypertension need supervision, elderly people who live alone need to be accompanied by their families because their memory is starting to decline. Maintaining a healthy lifestyle is important to control high blood pressure, such as avoiding stress, exercising, not smoking and not drinking alcohol. This study aims to determine the role of the family in caring for the elderly with hypertension at the Melati Posyandu, Kumain Village, Tandun District. This study uses a descriptive quantitative research type, namely by using a questionnaire sheet that is distributed to the elderly. The results of the study of 63 respondents at the Melati Posyandu, Kumain Village, Tandun District showed that the family plays a very important role in caring for the elderly. 58 respondents (92%) with the role category, 5 respondents (8%) with the role category. The suggestion of this study is that the elderly maintain habits that can control blood pressure so that it does not rise, one of which is by getting regular treatment at the elderly health post